[PCL-b-P(THF-co-CL)]m multiblock copolymer synthesized by Janus polymerization. (16th October 2017) - Qiu, Huan; Yang, Zhening; Shah, Muhammad Ijaz; Mao, Zhengwei; Ling, Jun
Abstract: Multiblock copolymers (MBCPs) composing of poly( ε -caprolactone) (PCL) and poly(tetrahydrofuran- co - ε -caprolactone) (P(THF- co -CL)) segments are synthesized in a one-step process by "Janus polymerization", a newly raised synthetic protocol. Janus polymerization includes an anionic and a cationic ring-opening polymerization on both ends of a single living polymer chain, and finally couples into MBCPs. The well-defined MBCPs have relatively high molecular weights up to 131 kg/mol and exhibit thermoplastic elastic property with excellent elongation of 2610% in tensile tests. The repeating blocks form phase separation structures observed by AFM responsible for the elasticity. The biodegradable elastomers have negligible cytotoxicity. According to the physiochemical properties observed in this work, such multiblock elastic poly(ether-ester)s are promising materials in many fields. Graphical abstract: Highlights: High molecular weight multiblock copolymers (MBCPs) are synthesized by a one-step methodology named Janus polymerization. The well-defined MBCPs exhibit excellent thermoplastic elastic property in tensile tests. Different microphase separation behaviors are observed by AFM responding to composition and heating histories.